(untitled) (Research, Society and Development, 2021)
It is reported a case of sporotrichosis in a mixed breed male feline of four months old and who had no partner or access to the street, in which there was an apparent human involvement. Edematous, ulcerative lesion with necrotic spots and serosanguineous exudate in the digit of the right thoracic limb was verified. The cytopathological examination revealed the presence of yeast-like cells compatible with Sporothrix sp. The radiographic examination showed osteolysis in the digit mentioned. The isolated administration of itraconazole proved to be effective in the treatment. Complete remission of the lesions occurred within 12 weeks. The tutor was referred for medical care and was duly treated. Sporotrichosis requires a prolonged time of treatment and clarification from owners about the care in handling the animal. The tutors showed resistance to attending clinical follow-up appointments, what probably was aggravated by the positive diagnosis of SARS-CoV-2 in one of them.